The impact of the educational marriage-matching model on the household income gap - Huo, Congjia; Chen, Lingming (Frontiers in Psychology, 2023)
With the acceleration of the modernization process, China's marriage matching model has undergone tremendous changes. The mating model has changed from the "home-to-household pairing" as the main emphasis on the first-endowed characteristics represented by family background to the focus on the autonomous features characterized by personal ability. The popularization of compulsory education has increased the proportion of women in higher education, and the gender gap in education has disappeared. Education has become one of the essential selection criteria for homosexual marriages, and the proportion of homogenous educational marriages in the Chinese marriage market is increasing. Educational homogenous marriage has produced the "Matthew Effect" in the Chinese labor market oriented by the rate of return to education, which has exacerbated income inequality between families. The text is based on the China Comprehensive Social Survey (CGSS) data. It uses the Recentralized Impact Function Regression Method (RIF) to empirically test that the marriage structure under different educational backgrounds has widened the income gap in Chinese households. Propensity score matching was used to correct possible selection bias and estimate the net effect of marital education matching on household income gaps. Based on theory and empirical evidence, some reasonable suggestions are put forward to advocate diversified marriages, strengthen social security, and reduce the family income gap.